ANALYSIS OF VALUE FOR MONEY PERFORMANCE MEASUREMENT AT THE NATIONAL POPULATION AND FAMILY PLANNING AGENCY OF EAST LUWU DISTRICT - Selpin, Dwi; Yusuf, Marwah; Sudiasa, Valentino (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2022)
This study aims to measure the success of value for money (economy, efficiency and effectiveness) in the family planning program at the Office of Population Control and Family Planning in East Luwu Regency. The analysis technique used is descriptive quantitative, namely analysis based on calculations. The steps taken in this activity are (1) measuring the economy, efficiency and effectiveness in each activity in the family planning program, (2) determining the final value for each activity. Based on the results of the study, it showed that the performance of the family planning program at the Department of Population Control and Family Planning in East Luwu Regency obtained the predicate of success by using value for money performance measurement.